The Formation of a Supply Chain Strategy for the Scientific and Technological Development of the Russian Federation Regions - Gennadii Beliakov; Anatoliy Gretchenko; Anna Ryzhaya; Anastasiya Shpak; Sergey Belyakov (International Journal of Supply Chain Management, 2019)
There has been a substantial lag in the scientific and technological development of Russia. Supply chain strategy has become an increasingly important management tool to help organizations improve their business operations. Economic sanctions imposed by a number of countries concerning, first of all, the ban on modern technology transfer dictated the need for a fundamental revision of Russia’s model of economic development and brought the development of science and the creation of advanced technologies to the fore. The purpose of the article is to consider supply chain strategy for the scientific and technological development of Russian regions. The examples of Germany, Great Britain, the USA, and China are analyzed to summarize the advanced foreign experience and identify the features of the state management of scientific and technological development. Proposals for the formation of a strategic planning system for the scientific and technological development of Russian regions are formulated.